Implementation Solar Panel Systems in Households: A Practical Guide to Energy Savings - Sinurat, Zefanya (Indonesian Journal of Electrical Engineering and Electronics, 2024)
Recently, the increase in electricity usage has become a reality. In Indonesia, the discovery of renewable energy sources is becoming more frequent. One solution being implemented is utilizing solar energy through Solar Power Plants (PLTS). This journal discusses the implementation of solar panel systems in homes as a practical guide for energy savings. Through case studies of implementation in several homes, this journal presents practical steps in installing and managing solar panel systems. The journal will also discuss the economic benefits obtained through the implementation of this system. The research results indicate that installing solar panels can be an effective step towards achieving energy efficiency and contributing to global efforts to reduce carbon footprints.